Tafsir Konstitusi Negara Dalam Keadaan Darurat (State Of Emergency) Dalam Menghadapi Darurat Kesehatan Masyarakat - Basri Effendi (Jurnal Transformasi Administrasi, 2020)
Abstract, The Constitution has explicitly formulated on article 12 of the Year 1945 Constitution stating that:"The president declares a state of danger, the terms and the consequences of the danger state stipulated by law". In the practice of national organizing, things are not normal in organizing the life of the state, where the existing legal system is unable to accommodate the needs of the state and society so that it requires a separate arrangement to drive the functions of the State in order to run effectively to ensure the fulfillment of basic rights of citizens. One of the problems experienced by all the nations of the world today is the threat from the epidemic of a Covid-19 virus. The central and local governments take the policy by closing the central places of the economy, trade, education and entertainment venues that are based on the economy. Abnormal state condition due to pandemic corona unlocks the country's determination in danger/emergency. This becomes problematic when the concept of state in danger has not become a paradigm in the formation of legislation. Although the Constitution has stipulated that the conditions and consequences of danger are established by law, but there is no legislation that specifically regulates the state's concept stagnation in a state of danger that should be able to follow the development of empirical realities of one of the possibilities of public health emergencies. It is therefore necessary to re-interpretation of the state concept in an emergency to fill the void of legal mind in the face of problems in the country.